(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Inquadramento giuridico - 2. La nuova edizione delle Norme - 3. Conclusioni. The new Norms Regarding Delicts Reserved To The Congregation For The Doctrine Of The Faith. First considerations ABSTRACT: On December 7, 2021, the “third edition” of the Norms Regarding Delicts Reserved To The Congregation For The Doctrine Of The Faith issued by Pope Francis with a rescript of the previous October 8 was published. The text updates the Norms currently in force, issued by John Paul II in 2001 and modified by Benedict XVI in 2010, adapting them to the reformed Book VI of the CIC. The revision made it possible to incorporate the laws enacted in recent years regarding the abuse of minors by clerics and to regulate what has been followed by the Congregation itself. This work, indicating the legislative changes, offers some initial considerations.